1988
DOI: 10.1111/j.1471-4159.1988.tb02967.x
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Aminobutyric Acid and Pentobarbital Enhance 2‐[3H]Oxoquazepam Binding to Type I Benzodiazepine Recognition Sites in Rat and Human Brain

Abstract: 2-Oxoquazepam (2oxoquaz) is a novel benzodiazepine which shows preferential affinity for type I benzodiazepine recognition sites. In the present study, we analyzed the effect of gamma-aminobutyric acid (GABA), pentobarbital, and chloride ions on [3H]2oxoquaz and [3H]flunitrazepam ( [3H]FNT) binding to membrane preparations from rat and human brain. GABA stimulated [3H]-2oxoquaz and [3H]FNT binding in a concentration-dependent manner. The maximal enhancement produced by GABA on [3H]2oxoquaz binding was higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the mammalian brain, the binding of benzodiazepines is enhanced by GABA (Tallman et al, 1978;Karobath and Sperk, 1979;Regan et al, 1980;Unnerstall et al, 198 1 ;Corda et al, 1988), and, vice versa, benzodiazepines stimulate [ 3H]GABA binding (Costa and Guidotti, 1979;Skemtt et al, 1982;Biggio et al, 1984;Ferrero et al, 1984;Corda et al, 1986Corda et al, , 1987. A similar reciprocal regulation was also present in the TBPS binding in the eel brain indicated the presence of a single population of binding sites (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…In the mammalian brain, the binding of benzodiazepines is enhanced by GABA (Tallman et al, 1978;Karobath and Sperk, 1979;Regan et al, 1980;Unnerstall et al, 198 1 ;Corda et al, 1988), and, vice versa, benzodiazepines stimulate [ 3H]GABA binding (Costa and Guidotti, 1979;Skemtt et al, 1982;Biggio et al, 1984;Ferrero et al, 1984;Corda et al, 1986Corda et al, , 1987. A similar reciprocal regulation was also present in the TBPS binding in the eel brain indicated the presence of a single population of binding sites (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Accordingly, the "in vitro" addition of GABA enhances the specific binding of [3H]FNT, and, vice versa, diazepam stimulates the binding of [3H]GABA. This finding indicates that the two recognition sites in the fish brain are functionally linked and have a pharmacological regulation similar to that present in higher vertebrates (Tallman et al, 1978;Costa and Guidotti, 1979;Karobath and Sperk, 1979;Regan et al, 1980;Unnerstall et al, 1981;Skerritt et al, 1982;Biggio et al, 1984;Ferrero et al, 1984;Corda et al, 1986Corda et al, , 1987Corda et al, , 1988.…”
Section: Discussionmentioning
confidence: 78%
“…Changes in endogenous GABA levels are unlikely to be responsible either, since the membranes were thoroughly washed. Considering the possibility that BDZ 2 sites are less sensitive than BDZ, sites to the effect of CABA (Corda et al, 1988), we can speculate that the upregulation of BDZ receptors, following chronic Ro 15-1788 treatment, is likely to affect predominantly the BDZ 2 receptors. Finally, it is still an open question whether in our study the endogenous ligand(s) and modulator(s) could have been cofactors in reducing the GABA enhanced benzodiazepine binding.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that lormetazepam has 2.9 times higher affinity to BZP receptors in the cere bellum than those in the spinal cord (19). It has been also reported that zolpidem and oxoquazepam bind to type I BZP receptors in the brain (3,4).…”
Section: Measurement Of 36c1 Influxmentioning
confidence: 99%
“…Recently, various new types of anxiolytic drugs, both BZP derivatives and non-BZP derivatives, have been introduced (3,4). These new drugs have more potent and selective phar macological properties, especially possessing low or barely detectable muscle relaxation activity, as com pared with that of classical BZP.…”
Section: Cerebellummentioning
confidence: 99%